The role of conductive additives on the performance of hybrid carbon xerogels as electrodes in aqueous supercapacitors. (1st February 2019) - Canal-Rodríguez, María; Menéndez, J. Angel; Montes-Morán, Miguel A.; Martín-Gullón, Ignacio; Parra, José B.; Arenillas, Ana
Abstract: Three different hybrid carbon xerogels containing Graphene Oxide (AXGO), Micronized Graphite (AXMG) and Carbon Black (AXCB) were synthesized using an easy, fast and affordable method. These three additives were initially selected to improve the electrical conductivity of the pristine activated carbon xerogel (AX) thus expecting to improve its performance in aqueous supercapacitors. Capacitances of the corresponding devices were measured as a function of current density and results of the high and low charge transfer regime of the supercapacitors were discussed separately. In both regimes, the differences observed between the hybrid electrodes were analyzed on the basis of the concurrent influence of the micro and mesoporosity, surface chemistry and electrical conductivity of the materials. Accordingly, even though all the hybrid carbon xerogels showed higher electrical conductivities, only AXGO rendered a better performance than AX, showing the highest capacitances in the whole interval of intensities studied. Consequently, at 16 A g −1, the energy and power densities of the AXGO supercapacitors increased up to 16% and 97%, respectively, with respect to AX, and of 143% and 409%, respectively, with respect to a commercial activated carbon used as reference. The performance of AXCB and, especially AXMG was worse than AX supercapacitors due to a combination of inadequate pore size distributions and/or a poor surface chemistry. Finally, TEM analysis helped to understand the different way the three additives were affecting the nanostructure (and final properties) of the hybrid carbon xerogels. Highlights: Additive suspensions are incorporated into carbon xerogels during their synthesis. Electrical conductivity depends on integration of additives into the polymeric structure. Equilibrium between structure and chemistry in carbons is necessary for electrochemistry. Graphene oxide seems the best additive for carbon xerogels in electrochemistry.